Posttraumatic Stress, Posttraumatic Growth, and Religious Coping in Individuals Exiting Sex Trafficking. Issue 3 (26th May 2020) - Schultz, Tammy; Canning, Sally Schwer; Eveleigh, Elisha
ABSTRACT: Seismic suffering stemming from sex trafficking can also paradoxically prompt a process of transformation and adaptive coping strategies. We investigated the levels of and linkages between traumatic events (TEs), posttraumatic stress (PTS), posttraumatic growth (PTG), and religious coping (RC) in individuals exiting sex-trafficking who were enrolled in a problem-solving court program (CATCH Court) and whether the amount of time in the program was associated with the study variables. Simultaneous, multiple linear regression analysis and simple mediation analysis were employed. The majority of the participants experienced extremely high TEs and elevated PTS, as well as, moderately high levels of PTG. Participants reported engaging in both positive and negative religious coping (PRC, NRC) although PRC was used more frequently. TE, PTS, PRC, NRC, and Time in CATCH Court significantly predicted PTG, explaining 41% of the variance. Higher levels of PRC were positively associated with higher levels of PTG. NRC and PRC were not substantiated as mediators in the relationships between TE and PTS, and PTS and PTG, respectively, though the NRC model narrowly missed establishing confidence. The struggle with stressors and use of PRC may provide some individuals exiting sex trafficking ways of experiencing transformative changes. Clinical and problem-solving court implications are included.